Análise da propensão ao uso de aplicativos pelos cidadãos para acompanhar mandatos eletivos no Legislativo Brasileiro - Pavan, Jessica Natalia Souza [UNIFESP] (2019)
The citizens participation and the information and communication technologies advent boosted the development of initiatives which corroborate a greater popular accession. Given this, the Political Techs arise as a way of innovation and use of technology to facilitate the access to information and candidates choice analysis during the election and as a means of following and monitoring of the government actions and guidelines, assisting the participation process and civic engagement. This research had as goal to analyze the citizens propensity to the use of applications to participate of the electoral mandates at the Brazilian Legislative. The analysis approach of this thesis was based on quantitative and qualitative methodologies, using the technique of applying a presential questionnaire survey instrument (survey) and with open and closed questions with a sample of 467 individuals. From Duane, O’Reilly and Andreev (2014, p.324); Collier and Bienstock (2006); Kim and Sundar (2014); Pavlou (2003); Venkatesh et al. (2012), Vivek (2009) was created a theoretical model containing specific latent variables to be applied in this study. The obtained results validate the model and confirm that the selected constructs in the existent models to evaluate the propensity to the usage have a considerable power of explanation when adapted to the object of the research. All hypotheses were validated and the R² found was 71.1%, considered high (CHIN,1998). The relation between Engagement and Propensity to the usage which had higher β, which demonstrates to be an essential construct for the citizen to use applications with the purpose of participating in legislative mandates. Due to the difficulty in finding constructs focused on the public sector, it was necessary to adapt the engagement construct, focusing on studies related to Marketing. The sample is limited for addressing just young students. As a recommendation it is reflected on the need for actions which involve the popular participation as a guideline for managements and mandates, and the search for actions and projects which aim the expansion and approximation between State and Society.